Envelhecimento e fisioterapia: Um novo olhar sobre a relação com o paciente idoso - Bifulco, Ana Maria da Silva (2006)
This Master dissertation analyses the aged patient-physiotherapist relationship through the ageing conception of the physiotherapy students group in the final phase of the conclusion of the course. This study has tried to verify many dimensions about the ageing process and the elderly nowadays, as well as it has reflected the perception of the students about this subjects. We still have searched to analyse the relation established between elderly and physiotherapist in the therapeutic link formation, always considering the culture, and verify the participation of the professional in this relation as active individual to search correct conducts for this group of patients. For accomplishment of this research of qualitative nature, we have used five interviews of the students, both sex and age varying between 23 and 30 years old. The students have come from physiotherapy course of the a University Center in Osasco, and they are in the final phase of the course. We have analyzed and interpreted the student speak, always with theoretical references of the some consolidates Anthropology authors, such as Geertz, Mercadante, Beauvoir and others. We have associated the denied culture of the elderly, it has brought the elderly just as something biological, feeding the negative stigma that has linked elderly and disease. It has been verified that contemptuous character that the students have associated to elderly, it has brought a distorted vision of the aging, it has made difficult the relationship with the aged and consequently it has become difficult the adhesion of the patient to physioterapic treatment as well as results, it has been necessary to change the thought way of the society about ageing, extending this concept much more than something biological, creating a construction model of the ageing that can provide a conception more positive to something real such as elderly